Übertragung und Übernahme der Strafverfolgung - Böse, Martin (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Within the framework of international cooperation, states can transfer the conduct or continuation of criminal proceedings to another state (e.g. the suspect's home state). In Germany, however, this cooperation instrument is not regulated by law. The study analyses the existing legal framework in international and EU law as well as the corresponding regulations in Switzerland and the Netherlands and outlines a legal and procedural framework for this cooperation instrument.